Low-demand parenting : dropping demands, restoring calm, and finding connection with your uniquely wired child / Amanda Diekman. - Diekman, Amanda (Jessica Kingsley Publishers, 2023)
Parent to neurodivergent children and autistic adult, Amanda Diekman, outlines a parenting approach that finally lowers the bar for the whole family, enabling the equilibrium of the home to be restored. Low-demand parenting allows you to drop the demands and expectations that are making family life impossible and embrace the joyful freedom of living life with low demands. It can be a particularly effective approach for children with high anxiety levels including neurodivergent children. Amanda talks from experience and teaches you how to identify what the big, tiny and invisible demands are for your own child and gives you the step-by-step instructions on how to drop them. Full of practical resources and scripts that are easy to implement in busy everyday life, this book is your flashlight and your map to parenting your uniquely wired child. It will not tell you where to go, but it will help you find your way so you and your family thrive.